Forest-related research capacity in Eastern Africa: Burundi, Eritrea, Ethiopia, Kenya, Sudan, Tanzania and Uganda - Spilsbury, M.J.; Kowero, G.S.; Mukolwe, M.O.; Netzehti, A.; Legesse, W.W.; Nsengiyumva, O.; Kiwuso, P.; Sabas, E. (Food and Agriculture Organization of the United Nations, 2003)
Efficient applied research systems are those that achieve a good match between the priority research problems and the capacity required to solve them. Effective research systems make a difference to real life problems through the timely delivery of readily utilisable research-based solutions to user audiences. In many developing countries both efficiency and effectiveness are constrained. Commonly, there is a mismatch between the priority problems and the problems to which the available research capacity and resources are allocated. Similarly, research findings often fail to reach the audiences that could put them to their most effective use. To rectify this situation, not only is it important to identify sound research priorities but also to deploy the available capacity to address these priorities in an effective manner. Effective future deployment requires knowledge current installed capacity at organisational, national and regional levels. Such knowledge also has utility for the design and implementation of effective collaborative research initiatives and capacity building investments. In 2001/02 a survey of forty-seven organisations conducting forest-related research in the Eastern African countries of Burundi, Eritrea, Ethiopia, Kenya, Sudan, Tanzania, and Uganda, was conducted. General trends relating to research capacity in the region are highlighted and include: insufficient collaborative research; poor linkages between research and intended users; inadequate flow of information and access to scientific literature; low levels of remuneration for researchers and a lack of continuity in research programme support. Research is seldom geared to inform public policy, and whilst the 'informal' forestry sector is of great importance to local livelihoods in many African countries, related topics do not feature strongly in the national/regional research agendas. An issue of profound concern for future research capacity in Eastern Africa is the continued erosion of human technical capacity from HIV /AIDS. While there is still a considerable need to invest in the development of human resources and physical infrastructure at the organisational level, governments and development assistance agencies should attempt a multi-pronged strategic approach to improve the overall performance of research systems. At a national level, research organisations need to be held to higher levels of accountability for the delivery of utilisable research products that generate public benefits. A key means of improving the efficiency and effectiveness of research systems at both national and regional levels will be investments that improve access to information, improved communications, and greater collaborative efforts. Support to national and regional research networks and their communications infrastructure will be key components in such investments.